84.0k views
2 votes
Y=-2x-9
6x-5y=-19 using the substiotion method

User Bublitz
by
6.5k points

1 Answer

5 votes
Substitute y = -2x - 9 to the 6x - 5y = -19 equation
6x - 5(-2x-9) = -19, simplify the equation
6x + 10x + 45 = -19, rearrange the terms
6x + 10x = -19 - 45, combine like terms
16x = -64, divide everything by 16 to get x
x = -4; this can be substituted in the y = -2x - 9 equation
y = -2(-4)-9
y = -1
To check Substitute everything to the equation
6(-4) - 5(-1) = -19
-19 = -19

User Onaracs
by
5.6k points